Sessile Serrated Adenomas: How to Detect, Characterize and Resect - Michael X. Ma; Michael J. Bourke (Gut and Liver, 2017)
Serrated polyps are important contributors to the burden of colorectal cancers (CRC). These lesions were once considered to have no malignant potential, but currently up to 30% of all CRC are recognized to arise from the serrated neoplasia pathway. The primary premalignant lesions are sessile serrated adenomas/polyps (SSA/Ps), although traditional serrated adenomas are relatively uncommon. Compared to conventional adenomas, SSA/Ps are morphologically subtle with indistinct borders, may be difficult to detect endoscopically, are more prevalent than previously thought, are associated with synchronous and metachronous advanced neoplasia, and have a higher risk of incomplete resection. Although many lesions remain “dormant,” progressive disease is associated with the development of dysplasia and more rapid progression to CRC. As a result, SSA/Ps are strongly implicated in the development of interval cancers. These factors represent unique challenges that require a meticulous approach to their management. In this review, we summarize the contemporary literature on the characterization, detection and resection of SSA/Ps.